11‐4: Improvement of Ambient Contrast of Micro‐LED Devices with High Reliability. Issue 1 (29th May 2019) - Zhang, Ke; Yan, Siwu; Liu, Yibo; Han, Tingting; Cho, Wai Keung; Liu, Zhaojun; Kwok, Hoi-Sing
Abstract : Micro‐LEDs are attracting more and more attention recently due to the excellent electrical and optical properties. The performance of Micro‐LEDs in different environment becomes very important in order to meet the requirement of various applications or even multi‐function mode. However, for display, we found the reflection of ambient light from metal electrode will reduce the contrast ration seriously. Therefore, more researches have be done to solve this problem and maximize the strengths of Micro‐LEDs. Here, we report the fabrication of Micro‐LEDs with varied size from 200um pitch to 20um pitch. The devices performance under different environment have been tested, showing great stability and reliability. Besides, the ambient contrast ratio (ACR) has been investigated, and a reflection elimination method has been proposed as well. Besides, according to the comparison between mini‐LED display and Micro‐LED display, the relationship between metal electrode design and light reflection has been investigated. And a trade‐off method has also been proposed, showing great potential to improve the performance of Micro‐LED display.